Bullous pemphigoid and multiple myeloma: a case report - Mendes, Joana Catarina Santos (2022)
Introduction: Autoimmune bullous skin diseases are rare pathologies. Among these, bullous pemphigoid is the most common subepidermal autoimmune bullous disease. The concomitant occurrence of bullous pemphigoid and malignancy has been reported in the literature, however, the evidence of this association remains controversial. This case report aims to raise awareness of this pathology’s existence, and its possible association with malignancy, and highlight the importance of several characteristics of general practice/family medicine. Case description: A 73-year-old woman with a history of diabetes mellitus, high blood pressure, and recurrent depressive disorder. No alcoholic, smoking, or toxiphilic habits. She constitutes a unitary family. Throughout several medical appointments, she presented with skin lesions (initially nonspecific lesions and later on tense bullous lesions), associated with pruritus, constitutional symptoms, and anemia, which started almost at the same time. Diagnoses of bullous pemphigoid and multiple myeloma were made. She was treated with oral corticosteroid therapy and has achieved complete resolution of the cutaneous symptoms. She later started chemotherapy and that improved her constitutional symptoms. She remains autonomous, living alone, with good family support. Comment: Bullous pemphigoid is a skin condition that family physicians should be aware of. Its possible association with malignancy is not proven. However, in patients with a recent diagnosis of bullous pemphigoid, although the search for neoplasms cannot be recommended beyond the usual oncological screenings, we suggest that a comprehensive assessment should be carried out, especially if there are suspicious signs and symptoms. The exposed clinical case also highlights the importance of all the characteristics of general practice/family medicine.